Anti-rituximab antibodies in patients with refractory autoimmune nodopathy with anti-neurofascin-155 antibody - Bai, Yunfei; Li, Wei; Yan, Chuanzhu; Hou, Ying; Wang, Qinzhou (Frontiers in Immunology, 2023)
Background: Recent studies have reported that similar to other IgG4 autoimmune diseases, such as muscle-specific kinase antibody-associated myasthenia gravis, most anti-neurofascin-155 (anti-NF155) nodopathies respond well to rituximab treatment, regardless of the dosage. However, there are still a few patients for which rituximab is ineffective for unknown reasons. Currently, there are no studies on the mechanism of ineffective treatment with rituximab. Methods: A 33-year-old Chinese man presenting with numbness, tremor, and muscle weakness for 4 years was recruited for this study. Anti-NF155 antibodies were identified by cell-based assay and confirmed by immunofluorescence assay on teased fibers. The anti-NF155 immunoglobulin (IgG) subclasses were also detected by immunofluorescence assay. Anti-rituximab antibodies (ARAs) were quantitatively analyzed using enzyme-linked immunosorbent assay (ELISA), and peripheral B cell counts were determined by flow cytometry. Results: The patient exhibited anti-NF155 IgG4-antibody positivity. After the first round of rituximab infusion, the patient showed stratified outcomes with improvements in numbness, muscle weakness and ambulation. However, after three rounds of rituximab infusion, the patient’s symptoms deteriorated, and the numbness, tremor and muscle weakness returned. No obvious improvement was found after plasma exchange and another round of rituximab treatment. 14 days after the last treatment with rituximab, ARAs were detected. And the titers gradually decreased on day 28 and 60 but remained higher than normal. Peripheral CD19+ B cell counts were less than 1% within the 2-month period following the final rituximab administration. Conclusions: In this study, ARAs presented in a patient with anti-NF155 nodopathy undergoing rituximab treatment and showed an unfavorable impact on rituximab efficacy. This is the first case to report the occurrence of ARAs in patients with anti-NF155 antibodies. We suggest that ARAs should be tested early during the initial intervention, especially in patients who respond poorly to rituximab treatment. In addition, we believe it is necessary to investigate the association between ARAs and B cell counts, their effect on clinical efficacy, and their potential adverse reactions in a larger cohort of patients with anti-NF155 nodopathy.